GLOBAL MANAGEMENT AND GLOBAL CULTURE: A BIBLIOMETRIC REVIEW OF BUSINESS PRACTICES AND PERFORMANCE - Asmaraningtyas, Lussy Widia; Sriyono, Sriyono (Jurnal Pendidikan Ekonomi (JURKAMI), 2024)
This research discusses Global Management and Global Culture in the context of international business development. Through a bibliometric approach, this research evaluates related literature to understand the influence of global management and global culture on business practices and company performance. The main findings highlight publication trends that include digitalization, sustainability, diversity, and the concept of "globalization" as important elements in global management. The theoretical and practical implications of this research demonstrate the complexity of global management and its contribution to international management theory. Practical recommendations include the integration of cultural understanding in business strategy, the enhancement of intercultural competence, and the adoption of sustainable practices. Although this research provides an interesting perspective, there are limitations in the research design and methodology. Therefore, for future research, it is recommended to conduct more in-depth studies on the influence of specific cultures in business practices as well as explore unexplored areas in the literature to provide more comprehensive practical solutions in an increasingly complex global business environment.